ChemInform Abstract: β‐Ketophosphonates Formation via Deesterification or Deamidation of Cinnamyl/Alkynyl Carboxylates or Amides with H‐Phosphonates. Issue 18 (April 2016) - Zhou, Yao; Zhou, Mingxin; Chen, Ming; Su, Jihu; Du, Jiangfeng; Song, Qiuling
Abstract: The convenient copper/iron‐catalyzed aerobic oxyphosphorylation method allows the conversion of a wide range of esters and amides into β‐ketophosphonates.